Deed Signing in Front of PPAT: Feasibility Evaluation (Study of PPAT Working Area of West Jakarta Administrative City) - Bintang Parashtheo (Dinasti Research, 2025)
The signing of a deed before a Land Deed Official (PPAT) is one of the important stages in the process of transferring land rights regulated by Indonesian agrarian law. This study aims to evaluate the feasibility of the deed signing process before a PPAT in the working area of West Jakarta Administrative City. This evaluation includes compliance with legal procedures, the quality of PPAT services, as well as the suitability of documents and the legality of the deed made. Through a qualitative approach with descriptive analysis, this research examines the various factors that influence the feasibility of deed signing, including the PPAT's role in ensuring the validity and legality of the deed, as well as the challenges faced by the parties involved in the process. The results show that although most PPATs in West Jakarta have carried out their duties in accordance with applicable regulations, there are some obstacles related to the public's limited knowledge of legal procedures, as well as potential problems in document verification that affect the feasibility of signing the deed. Recommendations are given to improve the quality of PPAT services through regulatory development and increasing public legal awareness